(untitled) (Nepalese Horticulture, 2025)
Nepal is rich in cultural heritage and natural beauty and has a deep rooted tradition of using flowers in religious, spiritual and social ceremonies. With the rapid growth of the floriculture sector- comprising over 1,170 nurseries and generating transactions worth NPR 3.68 billion in 2023/24, flower consumption has surged, especially during the festive season. However, this flourishing industry faces a growing challenge: floral waste. Unmanaged floral waste contributes to environmental degradation, including methane emissions and chemical pollution of water bodies. This research attempts to review and survey the current status of floriculture in Nepal, quantify flower waste generation, survey waste flower recycling, and highlight the innovative recycling practices. Each year, an estimated 5,000 metric tonnes of loose flowers and garlands are used in Kathmandu alone, with only 2% being recycled. Some local startups in Kathmandu have pioneered eco-friendly incense production from discarded flowers, promoting sustainability and women’s empowerment. Furthermore, the study explored the future opportunities such as essential oil extraction, dye production, pigment extraction and preparation of biopesticides. With government support, especially the 2022 ban on plastic flowers, and increased public awareness, Nepal has vast potential to integrate floral waste management into a circular economy. Sustainable practices can turn floral waste into valuable resources, reduce import dependency and open new economic opportunities for rural and urban communities.